(untitled) (Indian Journal of Animal Production and Management, 2024)
The study was conducted to observe the effect of Aloe vera (Aloe barbadensis) and Amla fruit (Emblica officinalis) powder supplementation alone and in combination on growth performance of broiler chicken. Un-sexed, apparently healthy, day old broiler chicks (240 in number) were randomly allocated to four groups with four replicates having 15 birds in each. Broilers were fed ration as per BIS (2007) standards. The supplementation of Aloe vera and Amla fruit powder alone and in combination showed highly significant (P<0.01) effect on feed consumption, body weight gain and feed conversion ratio. The study revealed that the inclusion of Aloe vera at 1 per cent and Amla fruit powder at 1 per cent alone and in combination enhanced the overall growth performance of broilers.